Manajemen Pembelajaran Mata Kuliah Kewarganegaraan di Akademi Refraksi Optisi Surabaya - Anggrainy, Dian Novita; Setyowati, Sri; Riyanto, Yatim (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The learning process of Higher Education requires a system that regulates all components of learning in order to achieve the goals set. This study is a qualitative research that aims to describe the learning management of citizenship courses applied by the Academy of optical refraction Surabaya. The lecturer of citizenship course has done lesson planning by making RPS, organizing learning by dividing all teaching materials according to the number of meetings in one semester and determining the source of teaching materials used. In the implementation of learning courses lecturers have carried out the three stages of learning aitu preliminary, core and closing stages. Supervision of learning is carried out by the head of the Study Program through field observation to determine the suitability of the RPS made with the implementation of learning. Supervision of learning is also carried out by lecturers by conducting formative and summative evaluations. The Learning Management run by the lecturer of citizenship course has been running.